Assessment of Nutritional Potency and Pomological Traits in the Wild and Cultivated Varieties of Momordica charantia L. (Cucurbitaceae) - Beevy, Salma Suhara; Haseena Bai, Noor Muhammed (Annals of Tropical Research, 2015)
Nutrient composition in the fruits of cultivated and wild varieties of M. charantia viz, M. charantia var. charantia and var. muricata were evaluated to prioritize the wild accessions suitable for crop improvement programme. The nutritive value of the varieties were assessed in terms of the quantity of proteins, carbohydrate, vitamins, total sugar, reducing and non-reducing sugar and minerals like Na, Ca, Mg, Mn, Fe,Cu and Zn. The wild variety was found superior than the cultivar in terms of their nutrient content. The study recognized MC12, as the elite germplasm with highest concentration of Vit. E, B2, Cu and Ca and the accession MC10 as a rich source of carbohydrate, non-reducing sugar and Vit. B1. The accessions MC2, MC7, and MC15 were superior having higher concentration of protein, Vit. C and reducing sugar respectively. Correlation analysis was carried out to determine the relationship between fruit traits and nutrient composition. UPGMA dendrogram analysis suggests that the nutritional variation in the accessions was not determined by the fruit and seed morphology. However, a direct relationship between the nutrient contents and the fruit traits viz, fruit weight, length and fruit diameter was observed. The study recommends the accessions like MC12, MC7, MC10, and MC15 with high nutrient composition for bitter gourd breeding programme. The study emphasizes the conservation of the wild species, the rich sources of nutrients for crop improvement programme.